Network reconfiguration for loss reduction with distributed generations using PSO - Dahalan, W.M.; Mokhlis, Hazlie (2012)
This paper presents an effective method based on Particle Swarm Optimization (PSO) to identify the switching operation plan for feeder reconfiguration and optimum value of DG size simultaneously. The main objective is to reduce the real power losses and improve the bus voltage profile in the system while satisfying all the distribution constraints. A method based on PSO algorithm to determine the minimum configuration is presented and their impact on the network real power losses and voltage profiles are investigated. To demonstrate the validity of the proposed algorithm, computer simulations are carried out on 33 bus systems and the results are presented and compare with the Genetic Algorithm (GA) method.